2016
DOI: 10.1039/c6ra17607k
|View full text |Cite
|
Sign up to set email alerts
|

Metal free synthesis of tetrahydrobenzo[a]xanthenes using orange peel as a natural and low cost efficient heterogeneous catalyst

Abstract: In this work, a facile, efficient and metal free catalytic system has been developed for the synthesis of tetrahydrobenzo[a]xanthene derivatives via a one-pot three-component condensation of various aldehydes, 2-naphthol, and dimedone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…TEM images ( Figure 1 c,d) also exposed the squashy characteristic of the catalyst with mesoporous and microporous nature. The high absorbent nature of OPA which could provide a suitable morphology for adsorption of organic compounds and solvents along with the high basicity of the catalyst is believed to be responsible for its catalytic activity in PET glycolysis [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM images ( Figure 1 c,d) also exposed the squashy characteristic of the catalyst with mesoporous and microporous nature. The high absorbent nature of OPA which could provide a suitable morphology for adsorption of organic compounds and solvents along with the high basicity of the catalyst is believed to be responsible for its catalytic activity in PET glycolysis [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Though orange peel (OP) contains some important by-products and was traditionally used to obtain essential oils and flavouring compounds [ 39 ], such a level of consumption generates a huge amount of orange peel waste, which eventually ends up in landfills [ 53 ]. More recently, efforts have been made to utilize OP waste either as a carbon activated for catalyst support [ 54 ], as a heterogeneous catalyst for chemical transformations [ 55 , 56 ] and for the production of low-cost biodiesel [ 57 , 58 ]. However, to our knowledge, there is no report of biomass waste-derived heterogeneous catalyst for the depolymerization of PET waste.…”
Section: Introductionmentioning
confidence: 99%
“…The invention of LAIL@MNP material having Lewis acidic zinc species immobilized onto magnetic Fe 3 O 4 nanoparticle not only brought about a remarkable yield increment but also enable a quite simple work-up step for product isolation as well as catalyst recovery (entry 21). The effect of solvent on the studied reaction was also investigated, showing that low yield of product was observed with polar as well as nonpolar solvents (Table S2, † entries [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Synthesis Of Benzoxanthene Derivativesmentioning
confidence: 99%
“…Based on the above fundamental understandings, we reported herein the designation of a novel magnetic nanoparticleimmobilized Lewis acidic ionic liquid and its usage as a prominent catalyst for the preparation of benzoxanthenes and pyrroles, two important heterocyclic scaffolds commonly present in various bioactive natural products, agrochemicals, and pharmaceuticals. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Although a large number of catalytic procedures have been developed for quantitative synthesis of these heterocycles, the attempt of searching for a versatile catalyst fullling all green chemistry criteria, such as highturnover property, excellent recyclability, simplicity in handling and recycling, and the capacity of promoting reactions under mild condition, has been still an unsolved problem. The initial results from our screening effort to nd novel ionic liquid-based catalysts for certain organic reactions indicated that magnetic nanomaterial Fe 3 O 4 -supported Lewis acidic ionic liquid could be the best candidate most likely satisfying all mentioned requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known synthetic route toward xanthenes derivatives is the one-pot multi-component condensation reaction between β-naphthol, dimedone and arylaldehydes. Ceric ammonium nitrate 10 , proline triflate 11 , NaHSO 4 .SiO 2 12 , strontium triflate 13 , Zr(HSO 4 ) 4 14 , dodecatungstophosphoric acid 15 , iodine 16 , InCl 3 /P 2 O 5 17 and p-toluenesulfonic acid/ionic liquid ([bmim]BF 4 ) 18 , RuCl 4 19 , brønsted ionic liquid 20 , molecular iodine 21 , trichloroacetic acid 22 , sulfonic acid functionalized imidazolium salts 23 , imidazole or isoquinoline 24 , orange peel 25 , rice husk 26 and TBAF 27 are employed as catalysts to promote this reaction.…”
Section: Introductionmentioning
confidence: 99%